Effectiveness of Using Vibrating Watches to Tell Time for Deaf Children - Defpriyansah, Bayu; Taufan, Johandri (Universitas Negeri Padang, 2023)
This research was conducted by researchers at SLB N Muara Bungo. Based on the results of observations, deaf children are still not orderly with the time of changing hours of entry, rest and return. Therefore, the researcher wanted to try to test a tool to help deaf students to know the time change. The tool in question is a Vibrating Watch that can be attached to the hands of deaf children. This research method is an experimental method with a Pre-Exsperimenal design and uses a one group pretest-posttest design. If the pretest value is greater than the pretest, then the treatment has a positive effect. The pretest and posttest values are equal to Zhitung =-2,121a with a probability or Asymp Sig (2-tailed) = 0.034. The results of the data calculation use the Wilcoxon Sign Rank Test formula. After obtaining the probability value, find a comparison with the predetermined probability, whose value is α = 0.05. The results show that the probability of Zhitung is less than the set probability, which is (0.344 < 0.05). So it can be concluded that vibrating watches are not effective for knowing the turn of the clock for deaf children at SLBN Muara Bungo.